How Does the “Zero Waste” Vision Promote Enterprise Innovation? Evidence from a Quasi-Natural Experiment - Hua, Jiaqi (International Journal of Social Sciences and Public Administration, 2026)
Against the strategic backdrop of the “dual carbon” goal and ecological civilization construction, China’s “Zero-Waste City” pilot policy represents a key institutional innovation for advancing solid waste reduction and recycling. This paper empirically examines its microeconomic effects on corporate green innovation by adopting a difference-in-differences (DID) approach, with Shanghai and Shenzhen A-share listed firms from 2015 to 2021 as the sample.The results show that the policy significantly boosts green innovation among enterprises in pilot cities, and this conclusion holds after robustness checks. Mechanism analysis reveals that R&D personnel input plays a partial mediating role, while public environmental concern has no significant mediating effect. Heterogeneity analysis indicates that the policy-driven green innovation effect is concentrated in eastern-region and large-scale enterprises, rather than central-western and small- and medium-sized enterprises.This study enriches research on the microeconomic impacts of environmental regulation and provides empirical support for the nationwide implementation and optimization of the “Zero-Waste City” policy.